2019
DOI: 10.4236/jwarp.2019.1110075
|View full text |Cite
|
Sign up to set email alerts
|

Climate Trends of Temperature, Precipitation and River Discharge in the Abbay River Basin in Ethiopia

Abstract: Projecting future changes of streamflow in the Abby River Basin (ARB) is important for planning and proper management of the basin system. The current study conducted in five stations of the Abbay river basin, and investigated the annual temperature, precipitation, and river discharge variability using the Innovative trend analysis method, Mann-Kendall, and Sen's slope test estimator. The result showed a slightly increasing trend of annual precipitation in Assoa (Z = 0.71), Bahir Dar (Z = 0.13), and Gonder (Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recent study by [26] using CMIP6, North East Africa (NEAF) region shows an increasing precipitation trend in SSP5-8.5, while SSP2-4.5 and SSP1-2.6 had no uniform trend during these periods. However, several climate change studies showed that precipitation projections are full of uncertainty [72,73]. For instance, on the contrary of all the above results, [60], [67] reported declining trends of mean annual precipitation up to −10.8% under RCP4.5 and −19.0% under RCP8.5 by the end of the century.…”
Section: Model Selection and Future Climate Projectionmentioning
confidence: 94%
“…Recent study by [26] using CMIP6, North East Africa (NEAF) region shows an increasing precipitation trend in SSP5-8.5, while SSP2-4.5 and SSP1-2.6 had no uniform trend during these periods. However, several climate change studies showed that precipitation projections are full of uncertainty [72,73]. For instance, on the contrary of all the above results, [60], [67] reported declining trends of mean annual precipitation up to −10.8% under RCP4.5 and −19.0% under RCP8.5 by the end of the century.…”
Section: Model Selection and Future Climate Projectionmentioning
confidence: 94%
“…a study conducted in England and Wales found spatial patterns and inter-annual variability in river temperature regimes [36]. Another study in Ethiopia investigated temperature trends in the Abbay River Basin and observed a slightly increasing trend in annual temperature [37]. These studies emphasized the significance of comprehending the temperature dynamics in river basins and the potential consequences of climate change.…”
Section: The Water Quality Index (Wqi)mentioning
confidence: 99%
“…In the recent times, time series analysis has emerged as a powerful tool for the efficient planning and sustainable management of the scarce water resources. Time series analysis on hydrological and climatological data have been carried out in different parts of the world in the last century, for example, to analyze historic rainfall data trends (Brunetti et al 2000;De Luís et al 2000;Astel et al 2004; Kumar et al 2010;Bekele et al 2017;Mahtsente et al 2019), for stream flow data trends Fanta et al 2001;Adeloye and Montaseri, 2002;Alemaw and Chaoka, 2002;Chen and Rao, 2002;Cunderlik and Burn, 2002;Kahya and Kalayci, 2004;Cherinet et al 2019), and climate change impact detection (Yu et al 2002).…”
Section: Introductionmentioning
confidence: 99%